Unveiling Connections: A Thorough Analysis of Sustainable Development Goals Integration within the Spanish Physical Education Curriculum - Salvador Boned-Gómez; Alberto Ferriz-Valero; Andreas Fröberg; Salvador Baena-Morales (MDPI AG, 2023)
This study analyses the relationship between the physical education (PE) curriculum in secondary education in Spain and the Sustainable Development Goals (SDGs). The Physical education curriculum of compulsory secondary education, as well as the complementary materials, were analysed through document analysis. Although there is no explicit relationship, the analysis reveals links between curricular elements and SDGs targets, particularly with SDG 4 (Quality Education), 3 (Health and Well-being), and 5 (Gender Equality). Other SDGs, such as 10 (Reducing Inequalities) and 12 (Responsible Consumption), are less related. The social dimension of sustainable development is most closely linked to PE. A historical analysis of the treatment of sustainable development in PE curricula in Spain is also presented, examining how they have evolved over time. The manuscript helps clarify how teachers and researchers can mobilize competencies to address global challenges in students' lives as individuals and world citizens, fostering commitment and social responsibility. Furthermore, this work highlights the importance of integrating the SDGs into education and how PE can be a key tool in this process.